Hestia the Invisible - Holub, Joan; Williams, Suzanne, 1953- (Holub, Joan. Goddess girls, 2015)
"Hestia feels unseen at Mount Olympus Academy in this eighteenth Goddess Girls adventure" -- provided by publisher.